An Analysis of Dixit: Board Game Design Elements for the Deaf Community - Soehalim, Aurelia (Universitas Ciputra, 2026)
This study examines inclusive board game design as a vital medium to support social interaction and cross-modal communication within and outside of the deaf community, with a specific focus on children and adolescents. Communication barriers frequently marginalize deaf individuals, limiting their participation in socially interactive environments. To address this, the research utilizes a qualitative observational approach supported by extensive library research to identify key design elements that foster inclusivity. By applying the Mechanic-Dynamic-Aesthetic (MDA) framework, the study analyzes how specific gameplay structures can bridge the gap between deaf and non-disabled players. The findings indicate that board games prioritizing 2-way communication using clear visual medium, simple feedback, and interaction mechanics can effectively reduce linguistic barriers and encourage active, equitable participation. Ultimately, this research contributes to the field of inclusive design by providing practical considerations and a theoretical foundation for creating socially accessible board games that promote empathy and shared play experiences across diverse sensory abilities.